1990
DOI: 10.1080/00332747.1990.11024478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Capacity to Work of the Mentally Ill

Abstract: This study explored the relationship between psychiatric symptomatology and the functional capacity to work. Subjects were diagnosed using DSM-III criteria and were grouped into categories of psychotic or nonpsychotic, and disabled or nondisabled, in regard to adjudication for mental impairment from the Social Security Administration (SSA). There were significant relationships between disability status and work capacity, in the direction of better performance for the nondisabled subjects. This finding reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Despite attention to vocational rehabilitation supports to achieve work, there has been no satisfactory framework to assist in understanding why some persons with schizophrenia work competitively post-diagnosis, and why some don't return to paid work. Three general notions contribute to a partial understanding of work restoration in young adults: first, the presence of negative symptoms and cognitive impairments negatively affects competitive employment (Anthony, Rogers, Cohen, & Davies, 1995;Lysaker & Bell, 1995); second, possessing adequate social competence and a strong preference for paid work appear to predict motivation for job procurement and tenure at any age (Kee et al, 2003;Massel et al, 1990;Mueser et al, 2001); and third, status as a Social Security Disability Insurance (SSDI) recipient negatively affects competitive employment outcomes for those newly diagnosed (Ho, Andreasen, & Flaum, 1997;MacDonald-Wilson, Rogers, & Anthony, 2001). While it is important to pay attention to all contributions to work recovery, it is equally important to provide a systematized means to understand early work experiences, aspirations, career preferences and antecedents, and strategies that guide career development in the young adult prior to illness onset.…”
Section: Introductionmentioning
confidence: 99%
“…Despite attention to vocational rehabilitation supports to achieve work, there has been no satisfactory framework to assist in understanding why some persons with schizophrenia work competitively post-diagnosis, and why some don't return to paid work. Three general notions contribute to a partial understanding of work restoration in young adults: first, the presence of negative symptoms and cognitive impairments negatively affects competitive employment (Anthony, Rogers, Cohen, & Davies, 1995;Lysaker & Bell, 1995); second, possessing adequate social competence and a strong preference for paid work appear to predict motivation for job procurement and tenure at any age (Kee et al, 2003;Massel et al, 1990;Mueser et al, 2001); and third, status as a Social Security Disability Insurance (SSDI) recipient negatively affects competitive employment outcomes for those newly diagnosed (Ho, Andreasen, & Flaum, 1997;MacDonald-Wilson, Rogers, & Anthony, 2001). While it is important to pay attention to all contributions to work recovery, it is equally important to provide a systematized means to understand early work experiences, aspirations, career preferences and antecedents, and strategies that guide career development in the young adult prior to illness onset.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of work capacity among persons with severe, persistent psychiatric disorders, Massel et al (1990) also found no differences in symptom severity between disability income recipients and nonrecipients, and they discovered unexpected similarities in some areas of tested work capacity between the two groups. Work tolerance, performance, and grooming were significantly worse in the recipient group.…”
Section: Previous Researchmentioning
confidence: 99%
“…Little emphasis on being would increase overreliance on doing and/or having. Extremes in doing, for instance, can be found in type A personalities, whereas extremes in not doing can be found in some degrees in procrastinations and, at the extreme, in severe psychopathological disorders (Massel et al, 1990).…”
Section: Resultsmentioning
confidence: 99%